2008
DOI: 10.1007/s00125-008-0935-x
|View full text |Cite
|
Sign up to set email alerts
|

LR-90 prevents dyslipidaemia and diabetic nephropathy in the Zucker diabetic fatty rat

Abstract: Aims/hypothesis Previous studies have shown that LR-90, a new inhibitor of AGE formation, prevented the development of experimental type 1 diabetic nephropathy. In this study, we examined the effects of LR-90 in the Zucker diabetic fatty (ZDF) rat, a model of type 2 diabetes and metabolic syndrome, and investigated the mechanisms by which it may protect against renal injury. Methods Male ZDF rats were treated without or with LR-90 from age 13 to 40 weeks. Metabolic and kidney functions and renal histology were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…6). Diabetic glomerulosclerosis is characteristics of late diabetes and usually found in renal tissue of long-term diabetic rats and TGF-β1 was a key mediator of diabetic glomerulosclerosis [12][13][14]. In contrast, in our study, diabetic rats were induced only for 8 and 16 weeks, thereby no diabetic glomerulosclerosis was observed and intensive insulin treatment may be induced too early to observe the difference in the early and late treatment groups.…”
Section: Figmentioning
confidence: 57%
See 1 more Smart Citation
“…6). Diabetic glomerulosclerosis is characteristics of late diabetes and usually found in renal tissue of long-term diabetic rats and TGF-β1 was a key mediator of diabetic glomerulosclerosis [12][13][14]. In contrast, in our study, diabetic rats were induced only for 8 and 16 weeks, thereby no diabetic glomerulosclerosis was observed and intensive insulin treatment may be induced too early to observe the difference in the early and late treatment groups.…”
Section: Figmentioning
confidence: 57%
“…We last tested the expression of TGF-β1, which could stimulate p38 MAPK expression [12][13]. The mRNA levels of renal cortical TGF-β1 in the 8wDM and 16wDM groups were 1.50 ± 0.47 and 1.81 ± 0.83 fold higher respectively, in comparison to the 16wNC group (p<0.05).…”
Section: Figmentioning
confidence: 99%
“…This is most clearly demonstrated by the renoprotection which is seemingly afforded with HMG CoA reductase inhibitors [102,103,104]. Interestingly, the majority of the AGE inhibitors assessed in this review (table 1) have been reported to improve lipid profiles in diabetic patients [99], as well as in experimental models of diabetic complications [31, 33, 64, 67, 69, 79, 105, 106]. Effects of RAS blockers, sRAGE and TZDs in plasma lipids have not been previously reported.…”
Section: Metabolic Disturbancesmentioning
confidence: 99%
“…It is thought to reduce AGE accumulation via its potent metal chelating abilities and its interaction with reactive carbonyl species [65]. Moreover, its renoprotective benefits, such as improvements in albuminuria, creatinine clearance and glomerular sclerotic index, have been demonstrated in experimental models of both type 1 and type 2 diabetic nephropathy [64, 65]. …”
Section: Therapeutic Modulation Of Advanced Glycation End Productsmentioning
confidence: 99%
See 1 more Smart Citation